1983
DOI: 10.1149/1.2120008
|View full text |Cite
|
Sign up to set email alerts
|

A Neutron Powder Diffraction Study of α ‐ and   β ‐ PbO2 in the Positive Electrode Material of Lead‐Acid Batteries

Abstract: A neutron powder diffraction study of α‐normaland β‐PbO2 , both chemically prepared and electrochemically formed in cycled battery plates, was carried out to correlate the electrochemical activity of the lead‐acid battery with the atomic arrangement of the electrode constituents. Our results are consistent with the presence of hydrogen in the structure of β‐PbO2 , but the departure of the occupancy factors from stoichiometric values are not large enough to unambiguously establish whether there are lead or ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 12 publications
1
16
0
1
Order By: Relevance
“…Other cations may be incorporated in the lattice and influence its stability [13]. However, neutron diffraction studies did not prove evidence for the presence of Pb or O vacancies [14], and the general formula may be also expressed as: (Pb 4+ ) 1 À x/2 (Pb 2+ ) x/2 (O 2À ) 2 À x (OH À ) x or finally (Pb 4+ ) 1 À x/2 (Pb 2+ ) x/2 (O 2À ) 2 One must distinguish the preparation of PbO 2 according to the Planté formation process [15,16], i.e., by cycling a lead electrode in sulphuric acid, and the plating resulting from soluble Pb(II) species present in an electrolyte.…”
Section: Introductionmentioning
confidence: 98%
“…Other cations may be incorporated in the lattice and influence its stability [13]. However, neutron diffraction studies did not prove evidence for the presence of Pb or O vacancies [14], and the general formula may be also expressed as: (Pb 4+ ) 1 À x/2 (Pb 2+ ) x/2 (O 2À ) 2 À x (OH À ) x or finally (Pb 4+ ) 1 À x/2 (Pb 2+ ) x/2 (O 2À ) 2 One must distinguish the preparation of PbO 2 according to the Planté formation process [15,16], i.e., by cycling a lead electrode in sulphuric acid, and the plating resulting from soluble Pb(II) species present in an electrolyte.…”
Section: Introductionmentioning
confidence: 98%
“…A new refinement of the massicot structure is desirable since recent neutron and X-ray diffraction analyses of the dioxides of lead (Hill, 1982;Jorgensen, Varma, RoteUa, Cook & Yao, 1982;Santoro, D'Antonio & Caulder, 1983;Hill, Jessel & Madsen, 1984) have indicated that small changes in structure and Pb :O stoichiometry may play an important role in determining the electrochemical activity of lead oxides in a battery environment.…”
mentioning
confidence: 99%
“…However, it has been reported that (1) can accommodate isotropic broadening by adjustments to U and W (Santoro, D'Antonio & Caulder, 1983), and consequently the above relationship (3) was tested with the assumption that the correction constant, X, would compensate for the increased breadth of a general reflection relative to a hypothetical hkO reflection at the same 20.…”
Section: Resultsmentioning
confidence: 99%
“…Such broadening results in a departure from a Gaussian shape, and more flexible peak-shape functions have therefore been proposed (Young & Wiles, 1982). With respect to changes in H, although (1) has satisfactorily accommodated broadening effects for some samples (Santoro, D'Antonio & Caulder, 1983), a serious difficulty arises for crystallites with markedly anisotropic dimensions, such as for clay samples (Adams & Hewat, 1981), where crystallite broadening becomes a function of the scattering vector. This effect has been reported even for a ZnO sample (Langford, 1981).…”
Section: Introductionmentioning
confidence: 99%